Mathematical Self-Efficacy and Creative Thinking in Social Arithmetic: Insight from Junior High School students in Papua - Purwati; Benidiktus Tanujaya; Maryo Sopater Istia (Jurnal VARIDIKA, 2025)
Research on mathematical self-efficacy and creative thinking has grown in recent years. However, studies examining their interaction in fostering mathematical creativity remain limited. Understanding this relationship is crucial, as self-efficacy influences students’ responses to open-ended challenges and their ability to generate creative solutions. This research gap is particularly relevant in the context of Papua, where cultural and contextual factors shape students' thinking patterns and problem-solving strategies. This study investigates the relationship between students’ mathematical self-efficacy and their creative problem-solving ability within the context of social arithmetic, an area often underexplored. Anchored in Bandura’s social cognitive theory, self-efficacy is conceptualized as a key psychological construct that influences student engagement, strategy use, and persistence in mathematical tasks. Employing a descriptive-exploratory design with embedded qualitative insights, this study involved 72 eighth-grade students from West Papua. Data were collected through a validated Likert-scale questionnaire, open-ended problem-solving tasks based on Torrance’s creativity framework, and semi-structured interviews analyzed thematically. Results show that 52.8% of students had moderate self-efficacy, while 25% were classified as high. In creative problem-solving, students excelled in fluency and elaboration but struggled with originality and flexibility. A strong positive correlation was found between self-efficacy and creative thinking (ρ = 0.849, p < 0.001). These findings underscore the importance of designing instructional strategies that enhance both confidence and cognitive flexibility through contextualized, open-ended, and collaborative learning environments. .